Time course analysis of immunity-related gene expression in the sea cucumber Apostichopus japonicus during exposure to thermal and hypoxic stress. Issue 95 (December 2019) - Huo, Da; Sun, Lina; Zhang, Libin; Yang, Hongsheng; Liu, Shilin; Sun, Jingchun; Su, Fang
Abstract: Temperature and dissolved oxygen concentration are important abiotic factors that can limit the growth and survival of sea cucumbers by affecting their immune systems. As global warming intensifies, sea cucumbers are increasingly exposed to adverse environmental conditions, which can cause severe economic losses and limit the sustainable development of sea cucumber aquaculture. It is therefore important to better understand how sea cucumbers respond to environmental stress, especially with regard to its effects on immunity. In the present study, the time series of immunity-related gene expression in sea cucumbers under thermal and hypoxic stresses were analyzed separately. The expression trends of 17 genes related to the nuclear factor κB (NF-κB) pathway, the protease family, the complement system, heat shock proteins (HSPs) and the transferrin family during exposure to two stresses at eight time points were concluded. These genes have interconnected roles in stress defense. The expression levels of genes relating to the NF-κB pathways and HSPs were strongly affected in the sea cucumber thermal stress response, while melanotransferrin (Mtf), ferritin (Ft) and mannan-binding C-type lectin (MBCL) were affected by hypoxia. In contrast, complement factor B (Bf), myosin V (Mys) and serine protease inhibitor (SPI) were not that sensitive during the initial period of environmental stress. Similar expression patterns under both thermal and hypoxic stress for certain genes, including an increase in Hsp90 and decreases in lysozyme (Lys), major yolk protein (MYP) and cathepsin C (CTLC) were observed in sea cucumbers. Conversely, NF-κB and Hsp70 were differentially affected by the two stress treatments. Lysozyme-induced immune defense was inconstant in sea cucumbers coping with stress. A gene ontology (GO) analysis of the selected genes revealed that the most co-involved terms related to immunity and iron ion. Our analysis suggests that sea cucumbers demonstrate complex and varied immune responses to different types of stresses. This dynamic image of the immune responses and stress tolerance of sea cucumbers provides new insights into the adaptive strategies of holothurians in adverse environments. Highlights: Expressed trends of 17 immune genes under two stresses at 8 time points were concluded. Genes related to Nf-κB pathway, protease, complement system, HSP and transferrin family were coefficient to defense stress. Sea cucumber showed complex and different immune pattern towards different stresses. These dynamic images provide new insights into adaptive strategies in sea cucumber tolerance to adverse environment.